Collaborative Governance in Multi-Stakeholder Partnerships for Sustainable Village Development - Rexy Nakula Urbaningrum; Suherna Suherna; Ipik Permana; Merlinda Intan Fauziah; Rohadin Rohadin (PT Mattawang Mediatama Solution, 2026)
Sustainable village development requires governance frameworks that mobilize diverse stakeholders across state, market, civil society, and community spheres. This study investigates collaborative governance in multi-stakeholder partnerships for sustainable village development in Indonesia, focusing on how coordination mechanisms, power relations, and institutional arrangements shape development outcomes. Employing a qualitative design, data were gathered through in-depth interviews, FGDs, observation, and document analysis across three villages in West Java Province. Findings reveal that effective collaborative governance is characterized by inclusive deliberation, transparent resource management, and adaptive inter-organizational coordination. However, elite capture, information asymmetry, fragmented institutional mandates, and uneven stakeholder participation continue to impede transformative partnerships. Drawing on collaborative governance theory, symbiosis theory, and institutional commons theory, this study proposes a Governance Integration Model (GIM) that operationalizes participation, transparency, accountability, collaboration, and sustainability.